Legitimacy in an Age of Global Politics
XIII, 273 p. 5 illus.
Keywords: In spite of the lack of plausible alternatives to liberal democracy, the age of globalization has ushered in serious challenges to the democratic legitimacy of the nation state. The contributors in this collection explore the frontiers of normative and empirical legitimacy research, drawing upon a range of key conceptual and methodological issues.